A sensory characterization of some N‐heterocycles in model spirit matrix: Influence of ethanol and several chemical features on aroma perception. (10th January 2023) - Goullet, Agathe; Hanaei, Farnaz; Vallet, Nadine; Nonier, Marie‐Françoise; Vivas, Nathalie; Vivas, Nicolas; Picard, Magali
Abstract: The qualitative spirit ageing bouquet, developed during maturation in oak casks through a complex transformation process, can result in a broad palette of nuances where roasted and nutty aromas are often identified. Nitrogen heterocycles (pyrazines, thiazoles, pyrroles), produced during the heating step of the barrel‐manufacturing, contribute to the perception of these nuances. However, their specific sensory characteristics within the spirit matrix have been poorly studied until now. The current study consisted in an overall olfactory characterization of nine targeted N‐heterocycles molecules previously identified in oak wood and detected in spirits. In a first step, the olfactory perception thresholds (detection and recognition) were measured in a spirit model medium (23% hydroalcoholic solution, pH 4), revealing that the presence of ethanol at such level minimally affected the olfactory perception of the studied compounds. A first sensory description of the set of N‐heterocycles also highlighted a large spectrum of aromatic nuances, mostly related to the semantic field of wood (nut, roasted, smoky, spicy). In a second step, a profile of the key aromatic attributes of the studied molecules was compiled, on the basis of their corresponding intensity scores given by a trained expert panel. Principal Component Analysis followed by Hierarchical Cluster Analysis categorized the pool of N‐heterocycles according to their sensory similarities. The presence of ethanol in spirit model matrix did not affect detection and recognition thresholds of studied N‐heterocycles. Wood‐derived nuances accounted among the most representative aromas characterized the studied N‐heterocycles. Functionals groups carried out by the chemical ring modified the aromatic perception of N‐heterocycles. Abstract : The presence of ethanol in spirit model matrix did not affect detection and recognition thresholds of studied N‐heterocycles. Wood‐derived nuances accounted among the most representative aromas characterized the studied N‐heterocycles. Functionals groups carried out by the chemical ring modified the aromatic perception of N‐heterocycles.